Media authorship - Chris, Cynthia, 1961-; Gerstner, David A., 1963- (AFI film readers, 2013)
"Contemporary media authorship is frequently collaborative, participatory, non-site specific, or quite simply goes unrecognized. In this volume, media and film scholars explore the theoretical debates around authorship, intention, and identity within the rapidly transforming and globalized culture industry of new media. Defining media broadly, across a range of creative artifacts and production cultures--from visual arts to videogames, from textiles to television--contributors consider authoring practices of artists, designers, do-it-yourselfers, media professionals, scholars, and others. Specifically, they ask: - What constitutes "media" and "authorship" in a technologically converged, globally conglomerated, multiplatform environment for the production and distribution of content? - What can we learn from cinematic and literary models of authorship--and critiques of those models--with regard to authorship not only in television and recorded music, but also interactive media such as videogames and the Internet? - How do we conceive of authorship through practices in which users generate content collaboratively or via appropriation? - What institutional prerogatives and legal debates around intellectual property rights, fair use, and copyright bear on concepts of authorship in "new media"? By addressing these issues, Media Authorship demonstrates that the concept of authorship as formulated in literary and film studies is reinvigorated, contested, remade--even, reauthored--by new practices in the digital media environment"--